Development and psychometric validation of the 'Parent Perspective University of Rhode Island Change Assessment-Short' (PURICA-S) Questionnaire for the application in parents of children with overweight and obesity. Issue 11 (17th November 2016) - Junne, Florian; Ziser, Katrin; Mander, Johannes; Martus, Peter; Denzer, Christian; Reinehr, Thomas; Wabitsch, Martin; Wiegand, Susanna; Renner, Tobias; Giel, Katrin E; Teufel, Martin; Zipfel, Stephan; et al.
Abstract : Introduction: High prevalence rates of childhood obesity urgently call for improved effectiveness of intervention programmes for affected children and their families. One promising attempt can be seen in tailoring interventions according to the motivational stages of parents as 'agents of change' for their children. Evidence from other behavioural contexts (eg, addiction) clearly shows the superiority of motivational-stage dependent tailored (behavioural) interventions. For the time-efficient assessment of motivational stages of change, this study aims to develop and psychometrically validate a 'Parent Perspective Version' of the existing University of Rhode Island Change Assessment-Short, an instrument assessing the motivational stages based on the theoretical fundamentals of the Transtheoretical Model of Psychotherapy. Methods and analysis: In a multistep Delphi procedure, involving experts from the study context, the original items of the University of Rhode Island Change Assessment-Short Questionnaire will be transformed from the 'self-perspective' ('I am having a problem') to the parent perspective ('my child is having a problem'). Following item adaptation, the new version of the questionnaire will be psychometrically validated in a cohort of N=300 parents with overweight or obese children. Parents will be recruited within a multicentre and multisite approach involving private paediatric practices, specialised outpatient clinics as well as inpatient and rehabilitation sites. Analyses will include confirmatory factor analyses, internal consistencies (reliability) as well as convergent and criterion validity. Convergent validity will be analysed using subscales of the HAKEMP-90 Questionnaire, an instrument which has been shown to differentiate between 'state' and 'action' orientation of individuals. Ethics and dissemination: This study has been granted ethics committee approval by the University of Tuebingen (number 644/2014BO2). The results of this study will be released to the participating study centres and will be submitted to peer-reviewed journals and presented at international conferences. Trial registration number: VfD_PURICA-S_15_003607 .